1994
DOI: 10.2527/1994.7261487x
|View full text |Cite
|
Sign up to set email alerts
|

Foodservice industry market profile study: nutritional and objective textural profile of foodservice ground beef

Abstract: Ground beef patties of three types (regular, lean, extra-lean) destined for the foodservice industry were collected from foodservice purveyors in 12 cities equally distributed across six geographical regions of the United States to assess nutritional and objective texture characteristics. Patties were cooked on a foodservice-style clamshell grill to a well (approximately 80 degrees C) degree of doneness (internal temperature) for nutritional analysis and objective texture measurements. Single 5.08-cm2 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
2
6
2
1
Order By: Relevance
“…The fat content of ground beef sample was 13.58%. Our results were lower than the report of Johnson et al (1994).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The fat content of ground beef sample was 13.58%. Our results were lower than the report of Johnson et al (1994).…”
Section: Resultscontrasting
confidence: 84%
“…The composition of ground beef is about 18% lipids and its fatty acids content is divided into 46% saturated, 51% monounsaturated and 3% polyunsaturated (Johnson, Williams, Neel, & Reagen, 1994). The fat content of ground beef sample was 13.58%.…”
Section: Resultsmentioning
confidence: 99%
“…The lean ground beef collected in summer had a significantly higher fat content (14.4%) than samples collected during winter (12.4%; P < 0.01). In either case, the fat content of the lean ground beef collected in this study was lower compared to that reported by Johnson et al (1994) for lean ground beef produced for food service in U.S. (17.5% fat), or compared to Ratnayake et al (1993) in beef patties from a Canadian fast food restaurant (17% fat) or to Barrado et al (2008) who measured the fat content of cooked hamburgers bought from several fast food restaurants in Spain (35.8% fat). Although the management details to produce beef used in this study were unknown, we speculate that differences in the fat content between the two collection periods would have been influenced by the grade of animals and the location of cuts and trimmings used for making ground beef.…”
Section: Effect Of Collection Periodcontrasting
confidence: 80%
“…Contrariamente ao reportado na literatura [7,14], a força de cisalhamento dos hambúrgueres adicionados de gordura (F2) se apresentou maior (p<0,05) que a dos demais tratamentos (F1, F3 e F4) (Tabela 3). Isto pode ter sido devido, em parte, à presença de fibras de tecido conectivo na gordura ovina utilizada na formulação F2.…”
Section: Tabela 2 Composição Médiaunclassified